Hypersensitivity Assessment of Non-Carious Cervical Lesions After Treatment with Different Desensitizing Protocols: A Randomized Clinical Trial - Heiba, Mohamed Tarek; Haridy, Mohamed Fouad; Abo El Ezz, Ahmed Fawzy; Faisal, Amr; Fouda, Hoda (Journal of Neonatal Surgery, 2025)
Trial design This is a three-arm, parallel-group, randomized, controlled, superiority, double-blinded experiment with a 1:1:1 allocation ratio. Using the Visual Analogue Scale (VAS scale), this study compared the clinical efficacy of fluoride varnish and light-cured resin-based desensitizer and bioactive glass powder in treating dentin hypersensitivity (DH) in adults with cervical non-carious lesions over a six-month follow-up period. Methods 75 individuals with non-carious cervical lesions (NCCL) who met the predefined inclusion and exclusion criteria were randomly assigned to one of three parallel groups (n=25) based on the treatment they received. Group 1 received fluoride varnish for their NCCL, Group 2 received "Sylc® dry powder" with the help of a "AquaCareTM Twin" air abrasion unit, and Group 3 received light-cured desensitizer agent SHIELD FORCE PLUS (Tokuyama). All participants had a pre-operative hypersensitivity test, and only those patients whose VAS score indicated a level of discomfort equal to or more than five were accepted into the study. Using an air blast with a standardized length and pressure, hypersensitivity was evaluated both immediately following treatment and three months later. The VAS's ordinal data were represented by median and range values. The Friedman test of repeated measures and the Mann Whitney U test were used for intragroup and intergroup comparisons, respectively. The significance criterion was set at P ≤0.05 for each test. Results The application of fluoride varnish caused the considerably highest VAS, followed by the application of sylc powder air polishing and light-cured desensitizer. The overall effect of the three interventions revealed a statistically significant difference in the VAS score (p<0.001). Even while there was a notable statistically significant difference between the three interventions' baseline VAS scores within the two follow-up intervals, there was no statistically significant difference in the baseline records within each follow-up interval. Conclusions and Clinical relevance. A quick and long-lasting solution for NCCL hypersensitivity is a light-cured desensitizing agent. Conversely, fluoride varnish remains an effective treatment for dentin hypersensitivity, but it is unreliable when used only once.